Gender Perspectives in Countering and Preventing Radicalisation and Violent Extremism in Europe - Rosato, Valeria (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2022)
Within the general framework of counter-radicalisation policies, civil society is increasingly perceived as one of the main partners in the development and implementation of counter-radicalisation and prevention strategies. According to the European Commission, in order to effectively address violent extremism, it is necessary to adopt an approach that focuses on the most vulnerable through close cooperation with local communities and, in particular, civil society actors.Within this approach, families have been identified as a priority target for prevention by both policymakers and practitioners in the field of PVE/CVE (Preventing and Countering Violent Extremism). This is because the process of radicalisation of an individual inevitably also involves the family, the circle of friends, the community and the wider society. Moreover, within the family, a crucial role is assigned to the woman, as a mother, both in terms of her ability/possibility to intercept signs of radicalisation and as a mediator within the family and the community.The aim of this paper is to analyse how European countries have included a gender approach in their programmes to counter and prevent violent extremism, highlighting any criticalities and/or strengths.From the analysis of recent studies, it is clear that the many contradictions inherent in these programmes of PVE/CVE are beginning to emerge, in particular, it is highlighted how women are instrumentalised and how a process of gender stereotyping is paradoxically fed. The risk is that women’s role is identified and limited to that of a family member (as mother, wife, sister) and that these measures to counter violent extremism based on a “maternalistic” logic have a negative impact, not only on the effectiveness of the measures to counter radicalisation, but also on the real processes of female empowerment and, more generally, on women’s rights